Deprescriptivising folk theories: critical multilingual language awareness for educators in Pakistan. Issue 6 (2nd November 2021) - Manan, Syed Abdul; David, Maya Khemlani
ABSTRACT: This study examines the discourses of educators in Pakistan through the lens of Critical Multilingual Language Awareness (CMLA) to demonstrate how their lack of critical awareness reinforces and reproduces subtractive language policies and practices in a diverse multilingual setting. CMLA stands for the understanding of the social, political and economic struggles surrounding the use of languages (García, O. 2009, Bilingual Education in the 21st Century: A Global Perspective, 302. Oxford: Wiley/Blackwell). Drawing on data collected through interviews and a questionnaire survey, the study analyses why most educators tend to manifest the following orientations/tendencies: monoglossic ideologies, devaluing native languages/cultures, normative assumptions about contemporary sociolinguistic order, English-medium fever, and fallacious folk theories about plurilingualism and multilingual education. The study suggests some policy measures that could foster CMLA, which could in turn help create 'ideological and implementational spaces' for multiple languages, literacies, and identities in classroom (Hornberger, N.H. 2003. Continua of Biliteracy: An Ecological Framework for Educational Policy, Research, and Practice in Multilingual Settings . Clevedon: Multilingual Matters, Hornberger, N.H. 2016. Researching the continua of biliteracy. In Research Methods in Language and Education, ed. K. King, Y.-J. Lai and S. May, 1–18. Cham: Springer International Publishing). We propose that deprescriptivisation and conceptual reorientation of educators could be crucial in this direction. This entails deconstruction of socially constructed folk theories about languages and language use, developing an awareness that 'language is socially created, and socially changeable to give voice and educate all students equitably' (García, O. 2017, Critical multilingual language awareness and teacher education. In Language Awareness and Multilingualism, ed. J. Cenoz, D. Gorter and S. May, 263–280. Cham: Springer International Publishing). We propose that language activists and critical applied linguists could play their agentive role as public intellectuals to deconstruct negative views about the role and value of the native/indigenous languages as pedagogical resources, and create ideological and political openings for inclusive perspectives, policies and practices. This could be achieved through scholarly activism, advocacy campaigns, and public awareness programs.